"The disadvantages of a defective education": identity, experiment and persuasion in the natural history of the salmon and parr controversy, c. 1825–1850. Issue 3 (September 2019) - Message, Reuben
Argument: During the second quarter of the nineteenth century, an argument raged about the identity of a small freshwater fish: was the parr a distinct species, or merely the young of the salmon? This "Parr Controversy" concerned both fishermen and ichthyologists. A central protagonist in the controversy was a man of ambiguous social and scientific status: a gamekeeper from Scotland named John Shaw. This paper examines Shaw's heterogeneous practices and the reception of his claims by naturalists as he struggled to find a footing on the "gradient of attributed competence" (Rudwick 1985 ). The case demonstrates the context-specific nature of expert-lay boundaries and identities and explores a range of material and linguistic resources available for negotiating them. Arguing for a view of Shaw's trajectory as simultaneously one of being a "practical man" and of becoming a naturalist, the paper explores both the permeability of social hierarchies in knowledge production and their effective role in the regulation of competency.